A Clinical Case Report on Cervical Cerclage (Journal of Pharmaceutical Negative Results, 2022)
Background: A common surgical treatment performed during pregnancy is cervical cerclage. It entails placing a suture (stitch) across the womb's neck (cervix), to provide the cervix with mechanical support and lower the risk of preterm birth. This procedure's electiveness and safety are still debatable. Presentation of the case the author presented a 30-year-old female who came to the tertiary hospital with a chief complaint of Amenorrhea, Nausea, and Vomiting in the last 6 Months. The patient had a history of infertility for 2 years, and they have taken infertility treatment in tertiary care hospital. Mechanical dilatation was done. Cervical dilatation 4.5cm. Cervical encerclage done. After 2 weeks USG report showed a bicornuate uterus single intrauterine fetus with absent cardiac Activity and fetal movement, average gestational age of 18 weeks 4 days, and corresponding to weight OF 249gms S/O fetal demise. After that abortus delivery was done under all aseptic precautions, a male abortus was delivered by Vertex presentation. The baby did not after birth. The baby did not show any signs of life after birth. The cord was clamped and the cut Placenta was delivered with intact membranes and cotyledons. Pack inserted, Uterine cavity exposed for clots and tears. Blood loss is minimal. Pack removed. 200 GMS of placenta delivered with intact membranes and cotyledons. APGAR- 0/10, 0/10, No Cry. Baby and placenta sent for HPE. Histopathology reports are awaited. She received treatment Inj C-Tax 1 Gm For 5 Days, Inj pan 40 mg 5 days, Inj doxy iv 2 days, Inj Emset 4 cc 2 days, tab Duvad 10 mg 3 days, Tab Ecosprine 150 mg 6 days, Tab Labet 100 mg days, Tab Dolo 650 mg 3 days, Tab Iron OD days, Tab calcium days, Protein powder 2tsp 4 days. After that patient was discharged and advised to the client's high protein diet, adequate fluids, not lifting heavy weight, not sitting cross legs for 1 month, and perineal hygiene. Tab Iron Od 3 Months, Tab calcium od months, protein powder 2 tsp 3 months.